Optimizing Sexual Education in Students SD Negeri 43 Pekanbaru City - Rika Mianna; Fatma Nadia; Rahmaniza Rahmaniza (PKM-P, 2023)
It is very important to introduce sex education to early childhood in order to protect children from violence or sexual abuse and bridge children's curiosity about things that lead to vulgarity. Sexuality education for children should be given when children ask questions related to this. Many of the research results suggest early sexuality education through activities in the community, especially in the world of education, bearing in mind that there are still many cases of sexual violence against children and continue to increase, plus in this modern era there are still many parents who are taboo about giving sex education to their children. their children, so it is expected that there is a need to optimize sex education. SD Negeri 43 Pekanbaru as a partner is one of the schools in the city of Pekanbaru, based on the discussion, the school said that sex education had never been carried out for their students and they would very much welcome anyone providing education about sexuality. The solution offered is by providing information about sex education through counseling and games methods, to determine the success of the education is carried out by giving pre-test and post-test before and after education. The pre and post-results show that there is a change in the mean between the pre-test and post-test with a difference of 0.404. Based on the statistical results, it was found that the p-value was 0.042, which was less than 0.05. It can be concluded that there is a difference between the value of sex education during the pre-test and post-test.